2019
DOI: 10.1016/j.dyepig.2019.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Polymorph dependent linear and nonlinear optical properties of naphthalenyl functionalized fluorenones

Abstract: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the work. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…The five polymorphs of 1-DNFO and 2-DNFO all exhibit extra-ordinary TPF at different wavelengths: 525, 542, 540, 567, and 561 nm for 1a, 1b, 1g, 2a and 2b, respectively. [96] For 1a and 1b, the 24 nm difference in TPF spectra coincides with that of the linear fluorescence spectra. TPF signals in these two noncentrosymmetric crystals behave differently upon a change of incident polarization.…”
Section: Dnfosupporting
confidence: 56%
See 3 more Smart Citations
“…The five polymorphs of 1-DNFO and 2-DNFO all exhibit extra-ordinary TPF at different wavelengths: 525, 542, 540, 567, and 561 nm for 1a, 1b, 1g, 2a and 2b, respectively. [96] For 1a and 1b, the 24 nm difference in TPF spectra coincides with that of the linear fluorescence spectra. TPF signals in these two noncentrosymmetric crystals behave differently upon a change of incident polarization.…”
Section: Dnfosupporting
confidence: 56%
“…By substituting the fluorenone moiety with 1-or 2-naphthalenyl units, Ju et al synthesized 2,7-di(naphthalen-1-yl)-9H-fluoren-9-one (1-DNFO) and 2,7-di(naphthalen-2-yl)-9H-fluoren-9-one (2-DNFO), where the fluorenone core has been extended (Figure 1h,i). [96] Five different crystals were grown out of these two molecules with significantly different morphologies: greenish yellow flake-like crystals (1-DNFO, referred to as 1a phase), brownish yellow needle-like crystals (1-DNFO, 1b phase), brownish yellow prismatic crystals (1-DNFO, 1g phase), orange rod-like crystals (2-DNFO, 2α phase), and yellow sheet-like crystals (2-DNFO, 2b phase). Among the five different crystals, the 1a and 1b phases are organized in noncentrosymmetric structures with orthorhombic Pca2 1 and monoclinic Pc space groups, respectively.…”
Section: Dnfomentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, due to the characteristics of high absorption intensity, narrow emission crest and easy modification, small organic molecules featuring electron Donor (D)-Acceptor (A) characteristics have been applied in near-infrared luminescent materials and devices. In our previous work, it was found that the intramolecular charge transfer compounds were assembled into ordered aggregations with a well-defined morphology by the non-covalent weak interactions at the supramolecular level, which could overcome the impact of fluorescence quenching caused by disordered aggregation of materials while also displaying characteristics of an optical waveguide [ 10 , 11 , 12 , 13 , 14 , 15 ]. To further study the intrinsic optical properties of such materials, an intramolecular charge transfer (ICT) compound with nitro-group acting as an electron acceptor and the nitrobenzothiadiazole unit as the electron donor was designed and synthesized.…”
Section: Introductionmentioning
confidence: 99%